Tri thức dân gian chăm sóc sức khỏe sinh sản cho phụ nữ và trẻ em người Phù Lá, Bắc Hà, Lào Cai - Chảo, Chử Chấn (Văn hoá thông tin, 2014)
Tri thức dân gian chăm sóc sức khỏe sinh sản cho phụ nữ và trẻ em người Phù Lá, Bắc Hà, Lào Cai